Field reports, Mark Proescholdt, spring 1991 - Proescholdt, Market al (1991)
Field reports form with few detailed descriptions of bird sightings submitted by Mark Proesholdt with several observers for spring 1991. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1991. Epson - sheet feed